RELATIONSHIP BETWEEN SOIL CHARACTERISTICS AND RATE OF SOIL LOSS ON COFFEE BASE-FARMING SYSTEM AT SUMBERJAYA, WEST LAMPUNG - DARIAH, AI; AGUS, F.; ARSYAD, S.; SUDARSONO, .; MASWAR, . (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2003)
The current public perception concerning land use change is, whenever forest is converted to agricultural land, the forest functions would drasticaly decrease. Studies have shown that soil loss in coffee based systems varied widely and it could be much lower than the tolerable soil loss level, depending on soil properties. This research was conducted to determine the dominant factors of soil properties in influencing soil loss. This analysis was based on data collected from a 3-site (Laksana, Tepus and Bodong Sub-Village of Sumberjaya Village, West Lampung) erosion study in 2001/2002. Observation of soil properties for each site was carried out by soil profile description and quantitative laboratory analyses for several soil physical properties and organic C content. Samples were collected from three soil depths namely 0-10, 10-20 and 20-40 cm. The resultsindicated that soil physical properties were dominant factors determining soil loss level in coffee-based farming system in Sumberjaya. The erosion on soil with mean total porosity of > 65%, macro pore of > 24%, and soil permeability of > 9 cm hr-1 was < 2 t ha-1 yr-1. Whereas erosion of soil with porosity of < 60%, macro pore of < 13%, and soil permeability of < 3 cm hr-1 was 37 t ha-1 for 3 months. These results suggested that soilconservation recommendation, particularly for Sumberjaya coffeebasedsystems, should not be imposed uniformly across sites. Site-specific soil property characterization and hence evaluation of soil susceptibility to erosion should precede recommendation and implementation emphasized only on erosion-prone sites.